Road works ahead: the journey of an innovative cross-campus hybrid learning space navigating higher education institutions’ organizational setbacks - De Caro-Barek, Veruska; Støckert, Robin (Frontiers in Education, 2024)
It has become pivotal for Higher Education Institutions to promote the implementation of both flexible study programs and related innovative learning environments to sustain learners’ lifelong education and the development of critical skills in an increasingly digitalized world. Innovation, however, has a cost. In Higher Education, innovation must necessarily reconcile academic advantages with economic conveniences. In this paper, we look in retrospect and share our experiences from a major research project linked to creating and implementing an innovative hybrid learning space within the frame of a cross-campus and cross-institution master’s degree based at two Norwegian universities. In the evaluation phase of the project, tension became apparent between the underlying pedagogical visions that sparked the enthusiasm for the project and the challenging reality of having to create, organize, and manage a complex cross-campus and cross-institution study program and build the learning space related to it. In two related publications, we specifically discussed the results from the project by focusing on the experiences educators and students collectively reported about working and studying in the ad hoc learning environment developed for the master’s program. We wish now to look back and explore the topic from an organizational perspective where the administration of the cross-campus and cross-institution project acts as a filter between the educators’ pedagogical vision and the students' experiences. In this exploratory case study, we have opted for a phenomenological investigation and a qualitative approach to research design that is informed by constructivist grounded theory methods. We went back to the educators’ and students’ feedback and tried to understand not just what worked and what didn’t, but why. We believe that sharing the experiences harvested from our project along the road can be of help to other researchers and stakeholders in confronting and finding solutions to the challenges that complex innovative projects might constitute for higher education institutions.